IMPROVING THE METHODOLOGY OF DEVELOPING CHILDREN'S VERBAL SPEECH BASED ON MORAL VALUES. (ON THE EXAMPLE OF A SCHOOL PREPARATORY GROUP) - Oripova Nodima Xalilovna; Meyliyeva Matluba Bayramali qizi (Journal Park Publishing, 2025)
This article explores the methodology of developing verbal speech in children of school preparatory groups through the integration of moral values. The research emphasizes the importance of speech development not only as a linguistic skill but also as a means of shaping a child's moral and ethical worldview. By incorporating moral narratives, value-laden dialogues, and culturally relevant storytelling, the methodology aims to foster both verbal competence and moral awareness.
Keywords: Verbal speech development, moral values, preparatory group, preschool education, character education, language acquisition, speech methodology, early childhood development, ethical communication, educational innovation.